MASCC/ISOO clinical practice guidelines for the management of mucositis secondary to cancer therapy. Issue 10 (25th February 2014) - Lalla, Rajesh V.; Bowen, Joanne; Barasch, Andrei; Elting, Linda; Epstein, Joel; Keefe, Dorothy M.; McGuire, Deborah B.; Migliorati, Cesar; Nicolatou‐Galitis, Ourania; Peterson, Douglas E.; Raber‐Durlacher, Judith E.; Sonis, Stephen T.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Mucositis is a highly significant, and sometimes dose‐limiting, toxicity of cancer therapy. The goal of this systematic review was to update the Multinational Association of Supportive Care in Cancer and International Society of Oral Oncology (MASCC/ISOO) Clinical Practice Guidelines for mucositis. METHODS A literature search was conducted to identify eligible published articles, based on predefined inclusion/exclusion criteria. Each article was independently reviewed by 2 reviewers. Studies were rated according to the presence of major and minor flaws as per previously published criteria. The body of evidence for each intervention, in each treatment setting, was assigned a level of evidence, based on previously published criteria. Guidelines were developed based on the level of evidence, with 3 possible guideline determinations: recommendation, suggestion, or no guideline possible. RESULTS The literature search identified 8279 papers, 1032 of which were retrieved for detailed evaluation based on titles and abstracts. Of these, 570 qualified for final inclusion in the systematic reviews. Sixteen new guidelines were developed for or against the use of various interventions in specific treatment settings. In total, the MASCC/ISOO Mucositis Guidelines now include 32 guidelines: 22 for oral mucositis and 10 for gastrointestinal mucositis. This article describes these updated guidelines. CONCLUSIONS The updated MASCC/ISOO Clinical Practice Guidelines for mucositis will help clinicians provide evidence‐based management of mucositis secondary to cancer therapy. Cancer 2014;120:1453–1461. © 2014 The Authors. Cancer published by Wiley Periodicals, Inc. on behalf of American Cancer Society.